The effect of crank position and backrest inclination on shoulder load and mechanical efficiency during handcycling. Issue 2 (19th September 2012) - Arnet, U.; van, S.; Schlüssel, M.; Lay, V.; van der, L. H. V.; Veeger, H. E. J.
<x xml:space="preserve">Abstract</x> Handbikes come in different models and setups, but only limited knowledge is available on the handbike‐user interface. The aim of this study was to identify optimal handbike setups, assuming that in such a setup mechanical efficiency is high, while shoulder load is low. Thirteen subjects with a spinal cord injury (paraplegia) performed handcycling with different handbike setups at constant power output: four crank positions (two distances, two heights) and four backrest inclinations. The O2‐consumption, kinetics, and kinematics were measured to calculate mechanical efficiency and shoulder load (glenohumeral contact force, net shoulder moments, and rotator cuff force). The analysis showed that more upright backrest positions resulted in lower shoulder load compared with the most reclined position [glenohumeral contact force (260 vs 335 N), supraspinatus (14.4% vs 18.2%), and infraspinatus force (5.4% vs 9.8%)], while there was no difference in efficiency. Except for a reduction in subscapularis force at the distant position, no differences in shoulder load or efficiency were found between crank positions. Recreational handbike users, who want to improve their physical capacity in a shoulder‐friendly way, should set up their handbike with a more upright backrest position and a distant crank placement.